Pengaruh Media Colour Board terhadap Kemampuan Mengenal Warna Anak Usia 5-6 Tahun di TK Aisyiyah Bustanul Athfal VII - Fitria Gia; Sri Wahyuningsi Laiya; Rapi Us Djuko (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Early Childhood Education Teacher Education, Faculty of Education. Supervisor I: Sri Wahyuningsi Laiya S.Pd, M.Pd, Supervisor II: Dra. Neat Kami Djuko M.Pd. The problem in this research is whether there is an influence of the "Color Board" media on the color recognition ability of children aged 5-6 years in Aisyiyah Bustanul Atfhal VII Kindergarten, North City District, Gorontalo City. The results of research with a sample size of 18 children show that there is a difference in the average pretest results. and Posttest. The experimental data results that have been detailed, the examination results or pre-test results before being given treatment have an average value of 18.88, while the post-test after being given treatment, the average value is 31.33. Thus, this research states that there is an influence of the "Colour Board" media on the ability to recognize colors in children aged 5-6 years at Aisyiyah Bustanul Atfhal VII Kindergarten, Kota Utara District, Gorontalo City. There is a need to develop skills in the ability to recognize colors, classify, differentiate and group. are several logical cognitive skills in early development and develop ways of thinking so that children can manage their learning gains, children also need to be taught to recognize colors from an early age so that children can develop knowledge about the importance of the concept of color which is closely related to the surrounding environment.